The Number of Pulses Needed to Measure Corticospinal Excitability by Navigated Transcranial Magnetic Stimulation: Eyes Open vs. Close Condition - Bashir, Shahid; Yoo, Woo-Kyoung; Kim, Hyoung Seop; Lim, Hyun Sun; Rotenberg, Alexander; Abu Jamea, Abdullah (Frontiers in Human Neuroscience, 2017)
Objective: Motor evoked potentials (MEPs) obtained by transcranial magnetic stimulation (TMS) enable measures of the corticospinal excitability (CSE). However the reliability of TMS-derived CSE measures is suboptimal due to appreciable pulse-to-pulse MEP amplitude variability. We thus calculated how many TMS–derived MEPs will be needed to obtain a reliable CSE measure in awake adult subjects, in the eyes open (EO) and eyes closed (EC) conditions. Methods: 20 halthy adults (70% male) received 40 consecutive navigated TMS pulses (120% resting motor threshold) in the EO or EC conditions on two separate days in randomized order. Results: For either the EO or EC condition, the probability that the 95% confidence interval (CI) derived from consecutive MEP amplitude measured included the true CSE increased when the number of consecutive stimuli increased (EO: p = 0.05; EC: p = 0.001). No significant effect of resting motor threshold, Mini-Mental Status Examination score, or gender on the CSE estimates was identified. At least 34 consecutive stimuli were required to obtain a most reliable CSE estimate in the EO condition and 31 in the EC condition. Conclusion: Our findings indicate that >30 consecutive MEPs may be necessary in order to obtain a CSE measure in healthy adults. Results: For either the EO or EC condition, the probability that the 95% confidence interval (CI) derived from consecutive MEP amplitude measured reflected the true CSE increased when the number of consecutive stimuli increased (EO: p = 0.05; EC: p = 0.001). No significant effect of rMT, Mini-Mental Status Examination score, or gender on the CSE estimates was identified. At least 34 consecutive stimuli were required to obtain a most reliable CSE estimate in the EO condition and 31 in the EC condition. Conclusion: Our findings indicate that >30 consecutive MEPs may be necessary in to obtain a CSE measure in healthy adults.